Social Media and the Reproduction of Violence A Critical Reading in Light of Bourdieu's Theory of Symbolic Violence (Al-Farooq Journal of Sciences, 2026)
This study aims to analyze the role of social media in reproducing symbolic violence through a critical sociological approach based on Pierre Bourdieu’s theoretical framework. The research adopts an analytical and critical methodology to examine digital space as a social field shaped by power relations and symbolic domination.The findings reveal that social media platforms significantly contribute to the reproduction of symbolic violence through various mechanisms, including digital discourse, user interaction, and algorithmic structures. Moreover, users themselves play a role in reinforcing this form of violence through their daily online practices.The study also highlights the psychological, social, and cultural impacts of symbolic violence in digital environments. It concludes by emphasizing the need for enhancing digital literacy, promoting critical awareness, and re-evaluating content regulation policies.